Book-trade networks in Siberia and the Far East: the history of initiation, present-day state and development trends (Part 2) - O. N. Alshevskaya (Библиосфера)
«Own» Siberian and Far Eastern networks formed by bookselling enterprises «Primorsk Trade House of Books» (1926), «Sibverk», (1991), «Mirs» (1992), «ProdaLit’» (1996), «Aristotel’» (2011) etc. determine the state of bookselling space in the region. By 2017, «ProdaLit’» is a powerful bookselling network with 54 stores (45 to 2000 m2, totaling 21697.5 m2) in four constituent entities of the Russian Federation (15 cities) and an Internet-shop. In 2016, the retail direction of the company was 67%, wholesale - 33%. The share of books in the company's turnover was 44.7% in 2015, and 43.2% in 2016. The company actively promotes the idea of a bookstore as a modern cultural and leisure center (CDC). The fate of the Far Eastern wholesale and retail network leader «MIRS» created in 1992 in Khabarovsk is similar in the history and present-day condition. In 2017, the network consisted of a head office in Khabarovsk, six wholesale branches, a distribution warehouse in Moscow, 63 storehouses (from 18 to 765 m2, in total, 16796.39 m2) in 16 cities and an online store. The contribution of the book assortment to the company turnover is about 30%. The company develops wholesale and retail directions; has introduced several bookstore formats into bookselling practice, the discount store «Plyushkin» (26 stores of 63 ones) has recently become the most prevalent. Each Siberian and Far Eastern cities with a population above 100,000 people has several local bookselling companies. The largest are: «Center-book» (Omsk, 12 stores), «City bestseller» (Krasnoyarsk, 26 stores and 7 departments), Svetlana (Irkutsk, 12 stores), Globus (Vladivostok, 7 stores), «Book Club Plus» (Tomsk, 7 stores), etc. The main characteristics of the regional network book trade are: · uneven development, unstable condition; · the greatest influence / significant effect of own regional networks on the local bookselling landscape: both through increasing the number of stores (retail), and providing logistics services to other booksellers in the region (wholesale direction); · creation and use of various formats of retail and wholesale-retail trade, as well as their combinations, taking into account the regional specifics; · diversification of activities; · organization of own online stores; · active propaganda of reading: stores become cultural and leisure centers; create and develop their own programs to support and develop reading and books; implement social projects; · raising competition with the market development. In general, significant, and sometimes determining, online bookselling companies effect on the regional bookselling landscape formation.